2012
DOI: 10.3109/07420528.2012.675253
|View full text |Cite
|
Sign up to set email alerts
|

Independent Effects of Sleep Duration and Body Mass Index on the Risk of a Work-Related Injury: Evidence From the US National Health Interview Survey (2004–2010)

Abstract: Fatigue has been linked to adverse safety outcomes, and poor quality or decreased sleep has been associated with obesity (higher body mass index, BMI). Additionally, higher BMI is related to an increased risk for injury; however, it is unclear whether BMI modifies the effect of short sleep or has an independent effect on work-related injury risk. To answer this question, the authors examined the risk of a work-related injury as a function of total daily sleep time and BMI using the US National Health Interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 52 publications
4
33
0
Order By: Relevance
“…One study showed that short self-reported sleep duration is linked to elevated BMI and may change appetite hormones [47] and in addition, a very recent study by Peltzer and Pengpid [59] confirmed an association between short sleep duration and increased BMI. In 2010, Lombardi et al [45] reported that poor quality or decreased sleep has been associated with obesity, this study's assumption supported by our observed finding; frequency of poor sleep was higher in over weight and obese participants as rate of 45.8% from all participants but still no statistically significant association was seen between poor sleep and body mass index of participants within the PSQI scoring. Otherwise, sleep quality and duration to fall into sleep in relation with BMI-as a single question-found nursing students only had statically association between sleep quality/duration to fall in sleep and BMI.…”
Section: Research Searching the Link Between Sleep And Bmi Amongsupporting
confidence: 82%
See 1 more Smart Citation
“…One study showed that short self-reported sleep duration is linked to elevated BMI and may change appetite hormones [47] and in addition, a very recent study by Peltzer and Pengpid [59] confirmed an association between short sleep duration and increased BMI. In 2010, Lombardi et al [45] reported that poor quality or decreased sleep has been associated with obesity, this study's assumption supported by our observed finding; frequency of poor sleep was higher in over weight and obese participants as rate of 45.8% from all participants but still no statistically significant association was seen between poor sleep and body mass index of participants within the PSQI scoring. Otherwise, sleep quality and duration to fall into sleep in relation with BMI-as a single question-found nursing students only had statically association between sleep quality/duration to fall in sleep and BMI.…”
Section: Research Searching the Link Between Sleep And Bmi Amongsupporting
confidence: 82%
“…[44] In 2010, Lombardi et al [45] mentioned that fatigue has been linked to adverse safety outcomes, and poor quality or decreased sleep has been associated with obesity. Moreover, objective measures of sleep showed that this pattern of disordered eating occurs during non-REM sleep and is associated with low sleep efficiency.…”
Section: Sleep Pattern and Body Mass Indexmentioning
confidence: 99%
“…A significant proportion of populations in developed countries in Europe and North America are obese (7), and obesity has also become more common in the developing world (8). Obesity is known to increase the risk of cardiovascular diseases and diabetes (8); lately obesity has been suggested as a risk factor for occupational injury (9)(10)(11)(12)5). Despite such observations, obesity's contribution to occupational injury risk remains far from clear in epidemiological literature.…”
mentioning
confidence: 99%
“…Sleep deprivation and poor-quality sleep is linked with lower productivity in the labor market (Williamson and Feyer 2000;Baldwin and Daugherty 2004;Landrigan et al 2004;Daley et al 2009;Lombardi et al 2012), increased health-care use (Redline and Newman 2002;Daley et al 2009), and increased risk of traffic accidents (Monk 1980;Hicks, Lindseth, and Hawkins 1983;Knipling and Wang 1994;Powell et al 2001). Sleep is believed to be linked with these outcomes through its impact on cognitive performance, decision-making abilities, memory, mood, reaction times, etc.…”
Section: Introductionmentioning
confidence: 99%